Assessment of Rice Inbred Lines and Hybrids under Low Fertilizer Levels in Senegal - Kanfany, G.; El-Namaky, R.; Ndiaye, K.; Traoré, K.; Ortíz, R. (MDPI, 2014)
This research was conducted at the Africa Rice Sahel Regional Station (near Saint Louis, Senegal) during two wet seasons (i.e., July to November) in 2010 and 2011 with the aim of assessing the performances of introduced hybrid cultivars along with an inbred check cultivar under low input fertilizer levels. The five treatments used in this study were (a) the control (without any fertilizer application), (b) 37.5–4.4–8.3 kg N–P–K ha−1, (c) half of recommend application in Senegal (75–8.75–16.5 kg N–P–K ha−1), (d) 112.5–13.3–24.8 kg N–P–K ha−1, and (e) the recommended application in the country (150–17.5–33 kg N–P–K ha−1). There were significant year and cultivar effects for all traits. The fertilizer levels affected significantly most traits except panicle length and 1000-grain weight. The year × fertilizer level and year × cultivar interactions were significant for most traits, but the fertilizer level × cultivar and year × fertilizer level × cultivar interactions were not significant. Days to maturity, plant height, panicle per m2, and grain yield increased with increasing fertilizer levels during the two wet seasons. The grain yield of rice hybrids (bred by the International Rice Research Institute) was not significantly higher than that of the check cultivar widely grown in Senegal. The assessment of other rice hybrid germplasm showing more adaptability to low fertilizer levels will facilitate further hybrid cultivar development in Africa.